Dynamic Relationship Between Water Resources and New Urbanization Based on a Vector Autoregressive Model: A Case Study of Hebei Province, China - Li, Shule; Yan, Jingjing; Pei, Qiuming; Sha, Jinghua; Liu, Fei (Frontiers in Environmental Science, 2022)
Overly rapid urban expansion in the past has significantly changed water resources, resulting in an imbalance between water resources and the sustainable development of new urbanization. To facilitate the sustainable development and utilization of water resources and promote the high-quality development of new urbanization, this study constructs evaluation index systems for water resources and new urbanization. The analytic hierarchy process, entropy method and projection pursuit method are used to determine the weight of each index, and Hebei Province is taken as an example for empirical analysis. The results indicate an upward trend for water resources in Hebei during the 2000–2019 period, while the water resources support capacity and water environmental pollution showed trends of gradual improvement but changed greatly, the water ecological carrying capacity gradually increased, and the negative impact of water disaster damage on the comprehensive situation of regional water resources gradually increased. Meanwhile, a qualitative breakthrough has been made in the development of new urbanization. Based on their evaluation results data, the long-term equilibrium relationship between water resources and new urbanization as well as the dynamics are empirically analyzed using a vector autoregressive model with a variable cointegration test, generalized impulse responses, and a decomposition prediction method using evaluation result data for the 2000–2019 period. There is indeed a supporting and inhibiting dynamic relationship between new urbanization and water resources as well as its components. At the early stage of urbanization, the endowment of water resources, the background value of the water environment, the ecological capacity of water and man-made water disasters were not fully considered, which led to the sharp contradiction between water resources and new urbanization. For a period, the decline in water resource support capacity and serious water environmental pollution have gradually become important factors limiting new urbanization in Hebei, and the constraining effects of the reduced water ecological carrying capacity and water disaster damage have gradually decreased. For future development, decision makers in Hebei should take measures such as adjusting the economic growth mode, improving resource utilization efficiency and technical level, and fully considering the positive role of new urbanization in promoting water resources and water environments. At the same time, Hebei Province should reduce the rate of water resource consumption by strengthening water conservation measures, optimizing the water utilization structure, and increasing investments in water pollution prevention and control to enhance the stability of water environments to realize the coordinated development of water resources and new urbanization.